1978
DOI: 10.1002/chin.197817023
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: STUDY OF THE ADSORPTION PROPERTIES OF PALLADIUM

Abstract: Durch potentiometiische Titration und Leitfähigkeitsmessungen werden die Adsorptionseigenschaften einer mit Pd überzogenen Pt‐Elektrode in verschiedenen Lösungen (0.1 N NaBr, KCl, Na,SO4, Cs2SO4, BaCl,‐) untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Thus far, the majority of the experimental results published in the literature were obtained by using combined voltammetric, amperometric, EQCM, impinging jet and radiotracer methods [4,6,8,9,[25][26][27][28][29][30]31]. For comparison, Fig.…”
Section: Overview Of the Most Important Experimental Results Reportedmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, the majority of the experimental results published in the literature were obtained by using combined voltammetric, amperometric, EQCM, impinging jet and radiotracer methods [4,6,8,9,[25][26][27][28][29][30]31]. For comparison, Fig.…”
Section: Overview Of the Most Important Experimental Results Reportedmentioning
confidence: 99%
“…The characteristic features common to Rh|(HClO 4 solution) systems are as follows [4,5,6,[25][26][27][28][29][30][31]:…”
Section: Overview Of the Most Important Experimental Results Reportedmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the inhibition in HClO 4 is much stronger, which requires special discussion. As PCA undergo reduction on Pt/Pt in the hydrogen range [12], the stronger inhibition in HClO 4 is presumably due to adsorbed products of the PCA reduction. As even small H 2 SO 4 additives in HClO 4 terminate the PCA reduction [12], to check the assumption on the role of these products, we added H 2 SO 4 in solutions of HClO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical reduction of perchlorate ion has been reported for a wide variety of cathodes, including platinum (Horányi and Vértes, 1975b;Vasina and Petrii, 1969), tungsten carbide Vértes, 1974, 1975a;Vértes and Horányi, 1974), ruthenium (Gonzales Tejera and Colom Polo, 1984), carbon doped with chromium(III) oxide or aluminum oxide (Mouhandess et al, 1980), aluminum (Kiss et al, 1973), and titanium Tsinman et al, 1975). Brown (1986) showed that chlorate and perchlorate may be reduced successfully to chloride by active titanium, and he discusses the possibility of passivation of the titanium electrode as titanium(IV) forms, presumably from the deposition of titanium dioxide.…”
Section: Kinetics and Thermodynamics Of Perchlorate Reductionmentioning
confidence: 99%